Of mutts and men [large type] - Quinn, Spencer (Quinn, Spencer. Chet and Bernie mystery, 2021)
"When Chet the dog and his partner, PI Bernie Little of the desert-based Little Detective Agency, arrive to a meeting with hydrologist Wendell Nero, they find that Wendell has come to a violent and mysterious end. Is his death a random robbery, or something more? Bernie might be the only one who thinks the police have arrested the wrong man, including the perp's own defense attorney. Chet and Bernie look into Wendell's work, a search that leads to a struggling winemaker who has received an offer he can't refuse. Meanwhile, Chet is smelling water where there is no water, and soon Chet and Bernie are in danger like never before." -- page [4] of cover.